Analysis of Power System and Drivetrain Component Design for Toyota Calya Electric Car - Putri Nabila Auliya; I Nyoman Sutantra (JMES The International Journal of Mechanical Engineering and Sciences, 2020)
The development of science and technology in automotive field increases as the time went by. The conventional vehicle nowadays has a negative impact on the environment, for example gas emmisions. To cope with the impact the innovation in electric vehicle (EV) is needed. In this research, there are three stages obtain a desired outcome: the data collection stage, the calculation stage, and the analysis stage. For the data collection, there are two methods; the experimental and the simulation stage. For the experimental, dynotest needs to be performed, while in the simulation is to obtain the data generated by Solidwork. In the calculation stage, the maximum speed, traction force, power generated, energy consumption, energy requirement, and slip and skid speed were calculated to obtain the desireable performance. Then, the analysis was performed to compare the performance of ICE and designed BEV and comply with the theories. The results from this research for converting ICE to BEV are re-design of the transmission and replace the engine into BLDC motor. The transmission needed for BEV is two-speed transmission while the motor used is 60 kW BLDC motor. The BEV can performs maximum climb-ability of 30◦ and reaches the maximum speed of 136 km/h in flat road while ICE only have climb-ability of 30◦ and same maximum speed as BEV. The energy consumption of BEV is 0.431 kW.h/km while ICE version is 0.539 kW.h/km. The battery used is Li-ion Ploymer 39 kW.h due to better specific energy and less toxic. For turning behavior, ICE have the safer driving behavior due to the center of gravity and understeer tendency than BEV. But the BEV still save to drive in certain turning speed.